The effect of nonrestorative sleep on incident hypertension 1-2 years later among middle-aged Hispanics/Latinos - Kaori Saitoh; Takuya Yoshiike; Yoshiyuki Kaneko; Tomohiro Utsumi; Kentaro Matsui; Kentaro Nagao; Aoi Kawamura; Rei Otsuki; Yuichiro Otsuka; Sayaka Aritake-Okada; Yoshitaka Kaneita; Hiroshi Kadotani; et al. (BMC, 2023)
Abstract Background Insomnia is known to be a major risk factor for incident hypertension. Nonrestorative sleep (NRS), which refers to insufficiently rested sleep, has reported to associate with various diseases. This study aimed to investigate the longitudinal association between insomnia-related symptoms including NRS and incident hypertension 1-2 years later by age group (young, 18-39 years and middle-age, 40-64 years) using existing cohort data involving Hispanics/Latinos. Methods This study included 1100 subjects who had participated in both the Hispanic Community Health Study/Study of Latinos and its follow-up study, the Sueño Ancillary Study, and met additional eligibility criteria. Incident hypertension was assessed by self-reported history and/or the use of antihypertensives. The Women's Health Initiative Insomnia Rating Scale (WHIIRS) was used to evaluate insomnia-related symptoms (difficulty initiating sleep, difficulty maintaining sleep, early morning awakening, difficulty returning to sleep, and NRS). Logistic regression analyses were conducted to assess the degree to which insomnia-related symptoms at baseline predicted incident hypertension. Results Among the participants (64% middle-aged, 36% young adults), 140 (12.7%) developed hypertension during the follow-up period. Among the sleep-related symptoms, only NRS predicted incident hypertension after adjusting for sociodemographic factors and physical condition (odds ratio: 1.88, 95% confidence interval: 1.10-3.21, p = 0.022) in middle-aged adults. None of the insomnia-related symptoms were associated with incident hypertension in the young adults. No association was found between WHIIRS-defined insomnia (total score ≥ 9) and incident hypertension in middle-aged adults or young adults. Conclusion The present findings suggest the importance of focusing on NRS to help prevent the development of hypertension in middle-aged adults.